Improving the Ability to Identify the Degree of Severity of Trauma by Nurses at the Peterongan Health Center Jombang Regency: Peningkatan Kemampuan Identifikasi Derajat Keparahan Trauma Oleh Perawat Di Puskesmas Peterongan Kabupaten Jombang - Prawito,S.Kep.,Ns.,M.Kep; Nanang Bagus Sasmito (Jurnal Kesehatan dr. Soebandi, 2022)
BackgroundDetermination of the severity of trauma patients as a basis for treatment to prevent worsening of the patient's condition, determining prognosis, the basis for determining appropriate treatment, as well as flagging or a sign of patients with the need for immediate resuscitation and immediate surgery. The purpose of this study was to measure the ability of nurses to identify the severity of trauma and evaluate the improvement in their abilities after an intervention in the form of learning and simulation.MethodThe method used in this study is a quasi-experimental study with a pretest-posttest design approach. The research will use the Peterongan Health Center in Jombang Regency. The total population is 26 nurses. Respondents used are 25 nurses. The sampling technique used is purposive sampling.ResultsPretest data on the ability of nurses to identify the severity of trauma showed that most (68%) were in the poor category. Posttest data on the ability of nurses to identify the severity of trauma showed that most (84%) were in the Good Category.AnalysisAnalysis of the data used in this study using the Wilcoxon sign Rank test showed the value of the 2 tiled sign of 0.000. This shows that there is a significant difference between the pretest and posttest data.DiscussionNurse's ability to identify severity. Measurements were carried out and identified based on the cognitive, affective and psychomotor domains. The ability of nurses increased after receiving interventions in the form of learning and training on simulation methods.Keywords: Simulation, Nurse Ability